2017
DOI: 10.4236/health.2017.913131
|View full text |Cite
|
Sign up to set email alerts
|

The Process of How Elderly Patients with Lung Cancer Who Are Receiving Molecularly Targeted Therapy with Oral Agents Establish Self-Management

Abstract: Purpose: In Japan, many elderly cancer patients are receiving chemotherapy using oral molecularly targeted drugs. They receive treatment in outpatient setting and have a need to self-manage at home. The purpose of this study was to clarify how elderly patients with lung cancer who are undergoing treatment with molecularly targeted drugs in outpatient setting establish self-management. Methods: The study used Kinoshita's Modified Grounded Theory. Semi-structured interviews were conducted with 17 patients (eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…In our previous study,[ 9 ] we identified the process by which elderly patients with lung cancer were able to achieve self-management. Based on the results, we examined what kinds of support were needed to facilitate the process of self-management.…”
Section: Development Of Self-management Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study,[ 9 ] we identified the process by which elderly patients with lung cancer were able to achieve self-management. Based on the results, we examined what kinds of support were needed to facilitate the process of self-management.…”
Section: Development Of Self-management Programsmentioning
confidence: 99%
“…In addition, our study revealed that elderly patients with lung cancer receiving molecularly targeted therapy with oral agents in an outpatient setting were able to self-manage based on their views of their own lives and the ways they wanted to live. [ 9 ] Furthermore, these patients need to receive appropriate help and information in accordance with how they wish to live their lives, which in turn makes it possible for them to manifest their strengths and maintain their lives based on personal choices. However, patients who are treated in an outpatient setting do not receive sufficient nursing support.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies had explored the factors affecting the occurrence and severity of skin ADRs. As shown by a study, male patients and elderly patients (over 65 years old) tended to experience more severe skin ADRs 19 , and patients with comorbidities had complicated disease conditions and took multiple medications, which easily led to severe skin ADRs or aggravation of ADRs 20 . In addition, the prolonged treatment period may also influence the degree of skin ADRs due to the toxicity of drugs accumulating over time 21 .…”
Section: Introductionmentioning
confidence: 99%